A Concise Synthesis of Azoxystrobin using a Suzuki Cross-Coupling Reaction. (October 2015) - Liu, Yong-Gan; Luo, Yan; Lu, Yao
A simple, efficient and eco-friendly process for the synthesis in good yield of azoxystrobin from 2-bromophenol has been developed using phenolic hydroxyl protection, Grignard reaction, Suzuki cross-coupling, hydrogenation and a nucleophilic reaction on a 2-chloropyrimidine.